This preview shows page 1. Sign up to view the full content.
Unformatted text preview: mary (3.13.4)
• For the general case, ay + by + cy = 0 , by assuming y (t) = e
rt we get the characteristic equation: ar + br + c = 0
2 • There are three cases.
i. Two distinct real roots: b2  4ac > 0. ( r1, r2 ) y (t) = C1 e r1 t + C2 e r2 t ii.A repeated real root: b2  4ac = 0. ( r ) y (t) = C1 e + C2 te
rt rt iii.Two complex roots: b2  4ac < 0. ( r1,2 = α±iβ ) Summary (3.13.4)
• For the general case, ay + by + cy = 0 , by assuming y (t) = e
rt we get the characteristic equation: ar + br + c = 0
2 • There are three cases.
i. Two distinct real roots: b2  4ac > 0. ( r1, r2 ) y (t) = C1 e r1 t + C2 e r2 t ii.A repeated real root: b2  4ac = 0. ( r ) y (t) = C1 e + C2 te
rt rt iii.Two complex roots: b2  4ac < 0. ( r1,2 = α±iβ ) y = eαt (C1 cos(β t) + C2 sin(β t)) Second order, linear, constant coeff, homogeneous
• Find the general solution to the equation y − 6y + 8y = 0
(A) y (t) = C1 e−2t + C2 e−4t (B) y (t) = C1 e2t + C2 e4t (C) y (t) = e2t (C1 cos(4t) + C2 sin(4t)) (D) y (t) = e−2t (C1 cos(4t) + C2 sin(4t)) (E) y (t) = C1 e + C2 te
2t 4t Second order, linear, constant coeff, homogeneous
• Find the general solution to the equation y − 6y + 8y = 0
(A) y (t) = C1 e−2t + C2 e−4t (B) y (t) = C1 e2t + C2 e4t (C) y (t) = e2t (C1 cos(4t) + C2 sin(4t)) (D) y (t) = e−2t (C1 cos(4t) + C2 sin(4t)) (E) y (t) = C1 e + C2 te
2t 4t Second order, linear, constant coeff, homogeneous
• Find the general solution to the equation y − 6y + 9y = 0
(A) y (t) = C1 e3t (B) y (t) = C1 e3t + C2 e3t (C) y (t) = C1 e3t + C2 e−3t (D) y (t) = C1 e + C2 te (E) y (t) = C1 e + C2 v (t)e 3t 3t 3t
3t Second order, linear, constant coeff, homogeneous
• Find the general solution to the equation y − 6y + 9y = 0
(A) y (t) = C1 e3t (B) y (t) = C1 e3t + C2 e3t (C) y (t) = C1 e3t + C2 e−3t (D) y (t) = C1 e + C2 te (E) y (t) = C1 e + C2 v (t)e 3t 3t 3t
3t Second order, linear, constant coeff, homogeneous
• Find the general solution to the equation y − 6y + 10y = 0
(A) y (t) = C1 e3t + C2 et (B) y (t) = C1 e3t + C2 e−t (C) y (t) = C1 cos(3t) + C2 sin(3t) (D) y (t) = e (C1 cos(3t) + C2 sin(3t)) (E) y (t) = e (C1 cos(t) + C2 sin(t)) t 3t Second order, linear, constant coeff, homogeneous
• Find the general solution to the equation y − 6y + 10y = 0
(A) y (t) = C1 e3t + C2 et (B) y (t) = C1 e3t + C2 e−t (C) y (t) = C1 cos(3t) + C2 sin(3t) (D) y (t) = e (C1 cos(3t) + C2 sin(3t)) (E) y (t) = e (C1 cos(t) + C2 sin(t)) t 3t Second order, linear, constant coeff, nonhomogeneous (3.5)
• Our next goal is to ﬁgure out how to ﬁnd solutions to nonhomogeneous
equations like this one: y − 6y + 8y = sin(2t)
• But ﬁrst, a bit more on the connections between matrix algebra and
differential equations . . . Som...
View
Full
Document
This note was uploaded on 02/12/2014 for the course MATH 256 taught by Professor Ericcytrynbaum during the Spring '13 term at The University of British Columbia.
 Spring '13
 EricCytrynbaum
 Differential Equations, Algebra, Equations

Click to edit the document details